2014
DOI: 10.1016/j.jiec.2013.10.064
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production from CO2 reforming of methane over high pressure H2O2 modified different semi-cokes

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Meanwhile, adding activated carbon (AC) into catalysts is also of great interest for improving the photocatalytic reaction. In other words, since low-cost AC has several advantages (e.g., high porosity, specific surface area, and excellent adsorption), catalytic performances could be improved during photocatalytic hydrogen production [34]. Additionally, many earlier studies reported that biomass AC could improve the catalytic ability for reformation of carbon dioxide [35] and enhance the energy-storage performances [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, adding activated carbon (AC) into catalysts is also of great interest for improving the photocatalytic reaction. In other words, since low-cost AC has several advantages (e.g., high porosity, specific surface area, and excellent adsorption), catalytic performances could be improved during photocatalytic hydrogen production [34]. Additionally, many earlier studies reported that biomass AC could improve the catalytic ability for reformation of carbon dioxide [35] and enhance the energy-storage performances [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Fossil fuel use in the transportation sector over the past century has experienced tremendous growth due to increases in the quality of life and the world economy. On the other hand, utilisation of fossil fuels in the transport sector contributed considerably to urban air pollution and now accounts for 29% of global greenhouse gas (GHG) emissions, which demands an urgent solution [1][2][3][4][5][6]. Hydrogen fuel cells have been considered as one of the best solutions for achieving zero-emission targets since the only product is water [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, research on methane conversion using various types of carbon materials has been conducted. Activated carbon [3], coal char [4], semi-coke [5] and bio-char [6] are mainly applied and used for these carbon materials. These studies have been extensively conducted mainly on the catalytic activity of the modified carbonaceous-based catalyst or the carbon material itself, and the characteristics of the reforming reaction for different operating conditions.…”
Section: Introductionmentioning
confidence: 99%